1984
DOI: 10.1136/bmj.289.6449.861
|View full text |Cite
|
Sign up to set email alerts
|

Return of splenic function after splenectomy: how much tissue is needed?

Abstract: Ninety patients whose spleen had been removed either because of trauma (41 cases) or as an elective procedure (49) were investigated for return of splenic function by counting pitted red cells and examining spleen scans made after injection of heat damaged 99mTc labelled red cells.There was no significant difference in the proportion of pitted red cells between the two groups of patients. Evidence of splenic tissue in scintiscans was not invariably associated with low pitted 'red cell values, suggesting that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
1
7

Year Published

1988
1988
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 26 publications
3
48
1
7
Order By: Relevance
“…Corazza et al reported a strong correlation between post{ splenectomy splenic tissue volumes and pitted red values. 34 Their data suggested that 20-30 cm 3 of splenic tissue was the critical value above which pitted cell counts fell below 16%. However, only one case report described a patient who survived pneumococcal sepsis; previously autotransplanted splenic fragments had grown up to five{fold.…”
Section: Discussionmentioning
confidence: 99%
“…Corazza et al reported a strong correlation between post{ splenectomy splenic tissue volumes and pitted red values. 34 Their data suggested that 20-30 cm 3 of splenic tissue was the critical value above which pitted cell counts fell below 16%. However, only one case report described a patient who survived pneumococcal sepsis; previously autotransplanted splenic fragments had grown up to five{fold.…”
Section: Discussionmentioning
confidence: 99%
“…The assumption that this indicates hyposplenism is based upon experience with a wide variety of disorders in older children and adults in whom impaired splenic function was confirmed by other methodologies (2,23,(41)(42)(43). It has been assumed that adult erythrocytes normally form these vesicles, which are then cleared by the spleen (15,23).…”
Section: Discussionmentioning
confidence: 99%
“…13 Com base nos achados clinicopatológicos dos implantes esplênicos espontâneos, o implante esplênico autógeno heterotópico passou a ser considerado como uma opção na tentativa de preservar as funções do baço, nos casos em que fosse inevitável a sua retirada. 4,[14][15][16][17] O auto-implante esplênico parece constituir a única alternativa para preservação de tecido esplênico após esplenectomia total. O objetivo deste trabalho foi analisar a depuração sangüínea da Escherichia coli nos órgãos do sistema mononuclear fagocitário (SMF) após esplenectomia total isolada ou combinada com auto-implante esplênico.…”
Section: Distribuição De Escherichia Coli Nos óRgãos Dounclassified